A critical study of presumed consent law in relation to organ donation in Malaysia / Halimaton Saadiah Abu Samah … [et al.] - Ibrahim Shukri, Nurul Iffah; Abu Samah, Halimaton Saadiah; Ahmad Shukkeri, Zainal Akmal; Hasmi, Mohd Syuwari Faiq (2013)
Organ Donation is a gift which involves a process of removal and transplantation of viable organ from donor to recipient. However, this is not a new area where throughout the world there is a gap between the demand and supply for organ transplants.1 In Malaysia, organ transplantation is governed under Human Tissues Act 1974 (Act 130), which allows using of body parts of the dead for therapeutic purpose, and for education and research. Unfortunately according to the World Health Organisation (WHO)'s Global Observatory on Donation and Transplantation (GODT) in 2010, Malaysia has one of the lowest cadaveric organ donation rates in the world at 0.7 per million populations (pmp). Hence, the aim of this study is to analyse on the inadequacies of the Human Tissues Act 1974 in resolving the low number of organ donors. Other than that, it will discuss on whether there is a need to review the informed consent system and trying to consider workability of presumed consent system in Malaysia. Thus, throughout the research comparisons will be made between Malaysia, Spain and Australia in which practicing presumed consent law and informed consent law respectively. Last but not least, this study will discuss the pertinent issues with regards organ donation in Malaysia in detail and come out with a several commentaries.